Reforma da previdência no serviço público civil: Diagnóstico dos estados e municípios - Bernardo Patta Schettini; Rogério Nagamine Costanzi (Instituto de Pesquisa Econômica Aplicada (IPEA), 2024)
– This Discussion Paper describes the changes brought about by the 2019 reform in the federal Public Employees' Retirement System (PERS) and the developments in the states, the Federal District and municipalities. Regarding the states and the Federal District, we analyze the details of the new benefit rules and the new financing conditions, drawing on the recent updates in their respective legislations. In the case of municipalities, we present an overview based on data from the tracking conducted by the federal government. Thus, we demonstrate that Constitutional Amendment No. 103 resulted in the proliferation of rules that are more lenient than the ones in effect for the federal employees among the 2,100 subnational governments that run PERS.
Keywords: H55; H75; J10; 330; pension reform; public employees; states and municipalities